Pemahaman Tekstual dan Kontekstual Hadis Larangan Mendirikan Bangunan Kuburan: Studi Kasus Makam Tuk Antan Dayun KM.70 Siak Riau - Fitri Wulandari; Muhammad Nuh Siregar (Lembaga Pendidikan Tinggi Nahdlatul Ulama (LPT NU) PCNU Kabupaten Nganjuk, 2026)
This study examines the dynamics of textual and contextual understandings of the hadith prohibiting the construction of structures over graves (bina’ ‘ala al-qubur), focusing on the case of the Tomb of Tuk Antan Darah Putih (Khalifah Khalil) in Dayun Village KM 70, Siak Regency, Riau. The study employs a qualitative design based on the living hadith approach, using case study and phenomenological approaches to religion. Primary data were collected through participant observation and in-depth interviews with traditional leaders, religious scholars, and local government officials. The findings indicate that, textually, hadiths narrated by Muslim and al-Tirmidhi prohibit plastering graves (tajshish), constructing structures over them (bina’), and inscribing them (kitabah) as an effort of sadd al-dhari‘ah to prevent practices that may lead to polytheism. Contextually, Shafi‘i jurists provide exceptions for the graves of righteous individuals and scholars for the benefit of pilgrimage and the preservation of religious symbols. The Dayun community responds to the hadith through two typologies: cultural pragmatism reflected in ancestral respect and historical preservation, and an accommodative-functional understanding rooted in traditionalist Islamic jurisprudence that emphasizes correcting pilgrims’ intentions. The tomb’s structure ultimately serves as a space for socio-religious negotiation between textual ideals and the realities of Malay-Islamic tradition in local religious practices amid ongoing transformation in modernity